Effect of artificial intelligence on economic growth in European countries: a symmetric and asymmetric cointegration based on linear and non-linear ARDL approach - Maha Kalai; Hamdi Becha; Kamel Helali (Journal of Economic Structures)
Abstract The impact of accelerated advancements in artificial intelligence (AI) on economic development remains a topic of debate in the current era. It is thought by some that AI has the potential to stimulate economic development; however, the precise function of AI remains uncertain. In order to investigate the influence of AI on economic growth in 30 European countries between 2000 and 2021, this study employed both the symmetric (PMG-ARDL) and asymmetric (PMG-NARDL) models. The ARDL model's results suggest that AI has a stimulating effect on economic development. A 0.217% increase in long-term economic growth is associated with an increase in AI. In the NARDL model, the growth of the economy was observed to be increased by 0.026% as a result of positive shocks to the positive AI variable. Conversely, negative shocks were found to have a negative impact, with a decrease of 0.029% in economic growth. It is posited that AI may stimulate economic development by increasing efficiency, promoting economies of scale, enhancing the quality of products and services, and improving working conditions. Furthermore, the study identifies the displacement of employment, the rising costs of training and adaptation, and the expansion of economic and social inequality. To address these challenges, policymakers must facilitate the creation of alternative employment opportunities, promote the development of new AI-driven industries, and implement rehabilitation programs for workers at risk of automation. Balancing technological advancement with job preservation and high-quality employment necessitates a collaborative approach between public and private sectors.